2018
DOI: 10.1103/physreve.97.052607
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoretic torque in colloidal particles with mass asymmetry

Abstract: We investigate the response of anisotropic colloids suspended in a fluid under a thermal field. Using nonequilibrium molecular dynamics computer simulations and nonequilibrium thermodynamics theory, we show that an anisotropic mass distribution inside the colloid rectifies the rotational Brownian motion and the colloids experience transient torques that orient the colloid along the direction of the thermal field. This physical effect gives rise to distinctive changes in the dependence of the Soret coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…In the case of a heavy bead, cos θ < 0 indicates that in this model, the heavy bead points towards the hot region. This is consistent with the results obtained previously for the same model [22]. Simulations of diatomic molecules, and binary mixtures, indicate that the heavy component accumulates in the cold region [15,33] Our result for the thermal orientation of the colloid shows that the response to the thermal gradient cannot be interpreted only in terms of the position of the heavy bead in the colloid.…”
Section: Thermomolecular Orientationsupporting
confidence: 92%
See 4 more Smart Citations
“…In the case of a heavy bead, cos θ < 0 indicates that in this model, the heavy bead points towards the hot region. This is consistent with the results obtained previously for the same model [22]. Simulations of diatomic molecules, and binary mixtures, indicate that the heavy component accumulates in the cold region [15,33] Our result for the thermal orientation of the colloid shows that the response to the thermal gradient cannot be interpreted only in terms of the position of the heavy bead in the colloid.…”
Section: Thermomolecular Orientationsupporting
confidence: 92%
“…It was concluded that these particles undergo anisotropic thermophoresis. Recently, it was shown that the internal composition of the particles, specifically a mass gradient, results in a thermophoretic torque [22]. The existence of this torque has been corroborated in both colloidal suspensions consisting of small and large colloids, relative to the characteristic diameter of the solvent molecules.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations